US national academy expels astronomer Geoff Marcy. (August 2021) - Gwynne, Peter
Abstract : The National Academy of Sciences (NAS) has rescinded the membership of exoplanetary astronomer Geoffrey Marcy. The action, which took effect on 24 May, comes six years after Marcy stepped down from his position at the University of California, Berkeley, for what he called "unwelcome behaviour with female graduate and undergraduate students".